1996
DOI: 10.1364/ao.35.006365
|View full text |Cite
|
Sign up to set email alerts
|

4 × 4 vertical-cavity surface-emitting laser (VCSEL) and metal–semiconductor–metal (MSM) optical backplane demonstrator system

Abstract: We describe a system demonstrator based on vertical-cavity surface-emitting lasers, metal-semiconductor-metal detectors, printed circuit board (PCB) level optoelectronic device packaging, a compact bulk optical relay, and novel barrel/PCB optomechanics. The entire system was constructed in a standard VME electrical backplane chassis and was capable of operating at >1.7 Gbit/s of aggregate data capacity. In addition to the component technologies developed, we describe operational testing and characterization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The VCSEL drivers and the electrical packaging used here were described previously. 14 The VCSEL drivers provide a constant bias current to raise the VCSEL's above threshold. Modulation of the optical intensity is then achieved by voltage modulation.…”
Section: A Vertical-cavity Surface-emitting Laser Array and Receivermentioning
confidence: 99%
See 1 more Smart Citation
“…The VCSEL drivers and the electrical packaging used here were described previously. 14 The VCSEL drivers provide a constant bias current to raise the VCSEL's above threshold. Modulation of the optical intensity is then achieved by voltage modulation.…”
Section: A Vertical-cavity Surface-emitting Laser Array and Receivermentioning
confidence: 99%
“…[11][12][13] Such VCSEL's have been demonstrated in several parallel data links. 2,3,14 To evaluate and demonstrate the suitability of 2-D optical interconnects based on VCSEL's and FIG's, it is necessary to address several issues. These include techniques to align the light emitted from the far end of the image guide with a detector array ͑many demonstrations to date have used singlechannel detectors or CCD cameras͒, the level of signal uniformity across multiple channels, the total optical power loss in the system, and the level of optical cross talk.…”
Section: Introductionmentioning
confidence: 99%
“…Recently several demonstrators such as an optical backplane, 7 an optoelectronic crossbar network, 8 an optical multimesh hypercube, 9 and the FAST-Net 10 were presented to exploit the potential applicability of the smart-pixel-based FSOI to parallel computers. These demonstrators aimed to show high capabilities of global interconnection with wide communication bandwidths in parallel-computing systems.…”
Section: Introductionmentioning
confidence: 99%
“…were used to demonstrate a board-to-board interconnection in an electronic backplane chassis. 8 Finally, work on free-space photonic-switching networks that used field-effect transistor self-electrooptic-effect devices 1FET-SEED's2 and complementary metal-oxide silicon (CMOS/SEED's) by McCormick et al 9 and Krishnamoorthy et al, 10 respectively, have demonstrated the connection-intensive capability of free-space optics.…”
Section: Introductionmentioning
confidence: 99%